Genomics and the challenging translation into conservation practice. (February 2015) - Shafer, Aaron B.A.; Wolf, Jochen B.W.; Alves, Paulo C.; Bergström, Linnea; Bruford, Michael W.; Brännström, Ioana; Colling, Guy; Dalén, Love; De Meester, Luc; Ekblom, Robert; Fawcett, Katie D.; Fior, Simone; et al.
Highlights There are few examples of genomic data being used in conservation biology. Many uncertainties accompany genomic analyses and interpretations. We discuss how best to deal with these uncertainties in a conservation setting. We outline why uptake has been difficult for practitioners and offer a solution.